Effect of microbial interaction on flavor quality in Chinese baijiu fermentation - Gao, Lei; Zhou, Jian; He, Guiqiang (Frontiers in Nutrition, 2022)
Chinese baijiu brewing is an open, complex, and synergetic functional microbiota fermentation process. Microbial interaction is pivotal for the regulation of microbial structure and function in the brewing microecosystem, consequently affecting the flavor and quality of baijiu. This article mainly summarizes the effect of microbial interactions among functional microbiota on the growth performance, flavor formation, and safe quality of baijiu fermentation process. In addition, the review specifically emphasizes on the microbial interactions for the regulation of “Ethyl Caproate-Increasing and Ethyl Lactate-Decreasing” in Chinese strong-flavor baijiu. Furthermore, the construction of synthetic microbiota by metabolic characteristics of the functional microbes and their interactions for regulating and controlling flavor quality of Chinese baijiu is also reviewed and prospected.